Analisis Perbaikan Jatuh Tegangan Pada Sistem Transmisi 150kV Gardu Induk Cerme Menggunakan Aplikasi Digsilent - Raka Trialviano Bagus; Denny Irawan (Universitas PGRI Palembang, 2023)
The electrical quality, especially voltage fluctuations, is very important to remain stable in supplying voltage to consumers. PT. PLN (Persero) has a minimum voltage limit of -5% and a maximum of +10% which is regulated in the Minister of Energy and Mineral Resources no. 3 of 2007 in the transmission system. However, the 150 KV transmission system often experiences voltage drops caused by conductors that are too long and inappropriate loads, so that in maintaining good transmission quality, a reliable system is needed. One of them is GI Cerme which has a double busbar type, which separates the two Java-Bali transmission sub-systems and is connected to supplies from West Surabaya GI and Lamongan GI. Even so, the Lamongan-Cerme network with a length of 26.77KMS and transformer load causes a voltage drop, in the case that occurred in April 2023 at GI Cerme at peak load it experienced a voltage drop of up to 137 KV, so it is necessary to overcome the voltage drop problem the transmission system was repaired at GI Cerme. Through the digsilent application, it is possible to simulate better system planning at GI Cerme so that the voltage can be repaired according to standards.